THE RELATIONSHIP BETWEEN SERVICE QUALITY, PERCEIVED VALUE, AND VISITOR SATISFACTION WITH REVISIT INTENTION TO MUSEUMS - Tiarmaida Sitohang; Ahmad Hudaiby Galihkusumah (SOSIOEDUKASI, 2026)
Museums are often considered attractions that are sufficient to visit only once. Therefore, understanding what elements can encourage museum visitors to return becomes important. This study aims to understand the influence of service quality, perceived value, visitor satisfaction, and revisit intention to museums. Data analysis in this study used SmartPLS 4.0 to test the relationships among variables based on survey data using a quantitative method. The model was tested for validity and reliability using Cronbach’s Alpha, Composite Reliability, and Average Variance Extracted values. The results show that service quality has a significant relationship with perceived value and visitor satisfaction. Perceived value has a positive impact on visitor satisfaction. Visitor satisfaction has the greatest impact on revisit intention. Visitor satisfaction as a mediator strengthens the relationship between service quality, perceived value, and revisit intention. This study implies that future researchers need to further explore the factors that make visitors feel satisfied and comfortable to revisit museums.